University of Florida Potato Variety Trials Spotlight: Elkton - Mario H. M. L. Andrade; Lincoln Zotarelli; Douglas Gergela; Kathleen Haynes (EDIS)
‘Elkton’ is a white-flesh potato variety suitable for chipping directly from the field (Figures 1 and 2). ‘Elkton’ was selected from the USDA-ARS breeding program in Beltsville, Maryland, by Dr. Haynes in 1997. In 2003, seed of ‘Elkton’ was made available for field evaluation under Florida growing conditions. In 60 trials conducted between 2003 and 2018, ‘Elkton’ yielded 112% in comparison with ‘Atlantic’ (Table 1). In these trials, ‘Elkton’ demonstrated resistance to internal heat necrosis and hollow heart, which are common tuber physiological disorders under high temperature growing conditions. https://edis.ifas.ufl.edu/hs1237